Recent HIV Infection among men who have sex with men and transgender women in Tijuana - Britt Skaathun; Heather A. Pines; Thomas L Patterson; Shirley J Semple; Jonathan Pekar; Alicia Harvey-Vera; Gudelia Rangel; Sanjay R. Mehta (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To characterize recent HIV infections among newly diagnosed men who have sex with men and transgender women in Tijuana. METHODS Limiting Antigen (LAg)-Avidity testing was performed to detect recent HIV infection within a cohort of newly-diagnosed men who have sex with men and transgender women in Tijuana. Logistic regression was used to determine characteristics associated with recent infection. A partial transmission network was inferred using HIV-1 pol sequences. Tamura-Nei 93 genetic distances were measured between all pairs of sequences, and the network was constructed by inferring putative transmission links (genetic distances ≤ 1.5%). We assessed whether recent infection was associated with clustering within the inferred network. RESULTS Recent infection was detected in 11% (22/194) of newly-diagnosed participants. Out of the participants with sequence data, 60% (9/15) with recent infection clustered compared with 31% (43/139) with chronic infection. Two recent infections belonged to the same cluster. In adjusted analyses, recent infection was associated with years of residence in Tijuana (OR = 1.5; 95%CI 1.01-1.09), cocaine use (past month) (OR = 8.50; 95%CI 1.99-28.17), and ever experiencing sexual abuse (OR = 2.85; 95%CI 1.03-7.85). DISCUSSION A total of 11% of men newly diagnosed with HIV who have sex with men and transgender women in Tijuana were recently infected. The general lack of clustering between participants with recent infection suggests continued onward HIV transmission rather than an outbreak within a particular cluster.